Dispersion stability of graphene nanoplatelets (GNPs) and noncovalent-functionalization of GNPs with chitosan in ethanol - Yaakub , Juliana; Mohamad, Noraiham; Abd Razak, Jeefferie; Lau, Kok-Tee; Abd Manaf, Mohd Edeerozey; Shueb, Mohammed Iqbal (Trans Tech Publications, 2015)
Abstract. A facile method for surface modification of graphene nanoplatelets (GNPs) in the presence of chitosan was developed to improve their interfacial interaction and dispersion within polymer matrix. The selection of a suitable organic dispersant for GNPs was performed using a sedimentation test of the GNPs in different organic media. GNPs exhibited the highest stability in ethanol dispersant after 3 weeks sedimentation test, and this was supported by TEM observation, which shows that GNPs dispersed well and fully exfoliated into individual sheets in ethanol. The dispersed GNPs in the ethanol dispersion were then functionalized with chitosan-acid solution, filtered and oven-dried into powder form for further characterization. FTIR spectra further verified that the formation of amide linkage between hydroxyl and carboxylic groups of GNP with the amide group of chitosan. The possible functionalization mechanism of GNPs with chitosan was also proposed.